Effects of high-frequency repetitive transcranial magnetic stimulation on the nutritional status of patients in a persistent vegetative state: A pilot study - Liu, Xuan-Wei; Zhao, Na-Na; Pang, Tao; Wen, Qiong; Xiao, Peng; Zeng, Ke-Xue; Wang, Dan-Ning; Chen, Jia-Min; Wang, Yu-Long; Yu, Hai-Bo (Frontiers in Nutrition, 2023)
Purpose This paper presents a preliminary study on whether repetitive transcranial magnetic stimulation (rTMS) can modulate the nutritional status of persistent vegetative state (PVS) patients (the primary endpoint) by regulating the intestinal flora and the metabolites, with the correlation between them also investigated. Methods Seventy-six patients with PVS were selected and divided into the observation group (n = 38) and the control group (n = 38) by random numerical grouping. All subjects’ stool samples were examined for metabolites and analyzed regarding the short-chain fatty acids (SCFAs) content. All subjects’ serum albumin, prealbumin, and hemoglobin levels were measured before and after the treatment. Nutrition risk screening 2002 was performed on all the subjects before and after the treatment and on the 30th and 90th days of the follow-up. Results (1) Intestinal flora structure: the Chao index, Ace index, and Shannon index of the observation group and the control group were significantly higher (p < 0.05), while the Simpson index was significantly lower (p < 0.05) following the treatment. (2) Metabolites of the intestinal flora: the observation group had significantly higher levels of acetic acid, butyric acid, and valeric acid (p < 0.05), as well as lower levels of propionic acid (p < 0.05) following the treatment. (3) Nutritional status (the primary endpoint): following the treatment, the above serum nutritional indices were significantly higher in both groups (p < 0.05), while the indices of the observation group were significantly higher than those of the control group (p < 0.05). Conclusion The rTMS method may improve the nutritional status of patients with PVS by regulating the structure of the intestinal flora and affecting the level of SCFAs through the microbiota–gut–brain axis. The possible mechanism involves how high-frequency rTMS can cause increased excitation in the frontal lobe of the right side of the brain, thus regulating the 5-hydroxytryptamine and norepinephrine levels.